Reducing heavy metals mobility in soil by natural plant extract - Ng, Teck Bin (2022)

(untitled)
In this study, the incubation experiment was conducted to assess the effect of plant extract (TM) application on the immobilization of Pb, Zn, Cr, Cu and Cd in soil. Soils was amended with 1 %, 2 %, 5 %, and 10 % of TM and incubated for 30 days. As a conventional organic stabilizer, rice husk derived biochar (RHB) had been applied in this experiment for comparison purpose. The fractions of each heavy metals (HMs) in soil were evaluated by Tessier’s sequential extraction procedure. The finding suggested that RHB had significantly increased the soil pH, SOM, and TOC while TM performed a negligible effect on soil pH and SOM but remarkably improved the soil TOC. Both stabilizers were found containing abundant of O-containing and N-containing functional groups by using ATR-FTIR. TM had successfully decreased the mobility of Cd and Zn by 11.28 % to 17.53 % and 4.77 % to 7.92 % with the increment of dosage. However, an increasing trend of Cu and Pb mobility in soil was observed after the application of TM. The mobility of Cu and Pb increased by 5.66 % to 8.20 % and 7.74 % to 10.84 % respectively. There was also found a fluctuated effect on Cr mobility with the increase of TM dosage and the difference was ranging from -0.88 % to 1.16 % when compared to control sample. It might suggest that TM was more suitable for Cd and Zn contaminated soil. In comparison, the performance of RHB was found more stable than TM, in which had decreased the mobility of Cd, Zn, Cr, Cu and Pb by ranging from 1.86 to 9.53 %, 8.77 to 11.96 %, 5.46 to 6.87 %, 2.94 to 13.97 %, and 1.16 to 7.48% respectively.